Local media, local candidates and preference formation - Javier Sajuria; Sofia Collignon (Political Research Exchange)
This study explores the role of local media consumption in shaping voter preferences for local candidates in electoral contexts. Drawing on the British Election Study (BES) data from the 2017 UK General Election, the paper examines how local media influences the preference for candidates with strong local ties. While previous research has established the electoral advantage of local candidates, this study delves deeper into the underlying mechanisms of preference formation, particularly focusing on media effects such as agenda-setting and framing. The findings reveal a nuanced relationship: although local media readership does not directly correlate with a preference for local candidates, its influence is conditional on the amount of time spent consuming media. Individuals who read local newspapers are initially more likely to prefer local candidates, but this effect diminishes as media consumption diversifies. This research highlights the complexity of voter behaviour and underscores the importance of local media in connecting political representation to geographically specific concerns. The findings contribute to the broader literature on electoral behaviour and media effects, offering insights into how localism and media environments interact to shape political preferences.